Late Onset Cobalamin Disorder and Hemolytic Uremic Syndrome: A Rare Cause of Nephrotic Syndrome - Gianluigi Ardissino; Michela Perrone; Francesca Tel; Sara Testa; Amelia Morrone; Ilaria Possenti; Francesco Tagliaferri; Robertino Dilena; Francesca Menni (Case Reports in Pediatrics)
Hemolytic uremic syndrome (HUS) is an unrare and severe thrombotic microangiopathy (TMA) caused by several pathogenetic mechanisms among which Shiga toxin-producing Escherichia coli infections and complement dysregulation are the most common. However, very rarely and particularly in neonates and infants, disorders of cobalamin metabolism (CblC) can present with or be complicated by TMA. Herein we describe a case of atypical HUS (aHUS) related to CblC disease which first presented in a previously healthy boy at age of 13.6 years. The clinical picture was initially dominated by nephrotic range proteinuria and severe hypertension followed by renal failure. The specific treatment with high dose of hydroxycobalamin rapidly obtained the remission of TMA and the complete recovery of renal function. We conclude that plasma homocysteine and methionine determinations together with urine organic acid analysis should be included in the diagnostic work-up of any patient with TMA and/or nephrotic syndrome regardless of age.